calcule sem 75° - cos 105°?
Soluções para a tarefa
Respondido por
16
sen (a+b) = sen a . cos b + sen b . cos a
sen (30 + 45) = sen 30° . cos 45° + sen 45° . cos 30°
sen (75°) =![\frac{1}{2}. \frac{ \sqrt{2} }{2} + \frac{ \sqrt{3} }{2} . \frac{ \sqrt{2} }{2} \frac{1}{2}. \frac{ \sqrt{2} }{2} + \frac{ \sqrt{3} }{2} . \frac{ \sqrt{2} }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B2%7D.+%5Cfrac%7B+%5Csqrt%7B2%7D+%7D%7B2%7D++%2B++%5Cfrac%7B+%5Csqrt%7B3%7D+%7D%7B2%7D+.+%5Cfrac%7B+%5Csqrt%7B2%7D+%7D%7B2%7D+)
sen 75° =![\frac{ \sqrt{2} }{4} + \frac{ \sqrt{6} }{4} \frac{ \sqrt{2} }{4} + \frac{ \sqrt{6} }{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Csqrt%7B2%7D+%7D%7B4%7D+%2B++%5Cfrac%7B+%5Csqrt%7B6%7D+%7D%7B4%7D+)
sen 75° =![\frac{ \sqrt{2} + \sqrt{6} }{4} \frac{ \sqrt{2} + \sqrt{6} }{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Csqrt%7B2%7D+%2B++%5Csqrt%7B6%7D++%7D%7B4%7D+)
cos (a+b) = cos a . cos b - sen a . sen b
cos ( 45 + 60) = cos 45° . cos 60° - sen 45° . sen 60°
cos (105°) =![\frac{ \sqrt{2} }{2} . \frac{1}{2} - \frac{ \sqrt{2} }{2} . \frac{ \sqrt{3} }{2} <br /> \frac{ \sqrt{2} }{2} . \frac{1}{2} - \frac{ \sqrt{2} }{2} . \frac{ \sqrt{3} }{2} <br />](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Csqrt%7B2%7D+%7D%7B2%7D+.++%5Cfrac%7B1%7D%7B2%7D+-++%5Cfrac%7B+%5Csqrt%7B2%7D+%7D%7B2%7D+.++%5Cfrac%7B+%5Csqrt%7B3%7D+%7D%7B2%7D+%3Cbr+%2F%3E)
cos 105º =![\frac{ \sqrt{2} }{4} - \frac{ \sqrt{6} }{4} \frac{ \sqrt{2} }{4} - \frac{ \sqrt{6} }{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Csqrt%7B2%7D+%7D%7B4%7D+-++%5Cfrac%7B+%5Csqrt%7B6%7D+%7D%7B4%7D+)
cos 105° =![\frac{ \sqrt{2} - \sqrt{6} }{4} \frac{ \sqrt{2} - \sqrt{6} }{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Csqrt%7B2%7D+-++%5Csqrt%7B6%7D+%7D%7B4%7D+)
Sen 75° - cos 105° =![\frac{ \sqrt{2} + \sqrt{6} }{4} - \frac{ \sqrt{2} - \sqrt{6} }{4} \frac{ \sqrt{2} + \sqrt{6} }{4} - \frac{ \sqrt{2} - \sqrt{6} }{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Csqrt%7B2%7D+%2B++%5Csqrt%7B6%7D+%7D%7B4%7D+-++%5Cfrac%7B+%5Csqrt%7B2%7D+-++%5Csqrt%7B6%7D+%7D%7B4%7D+)
Sen 75° - cos 105° =![\frac{ \sqrt{2} - \sqrt{2} + \sqrt{6} + \sqrt{6} }{4} = \frac{2 \sqrt{6} }{4} <strong>= \frac{ \sqrt{6} }{2} \frac{ \sqrt{2} - \sqrt{2} + \sqrt{6} + \sqrt{6} }{4} = \frac{2 \sqrt{6} }{4} <strong>= \frac{ \sqrt{6} }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Csqrt%7B2%7D+-++%5Csqrt%7B2%7D+%2B++%5Csqrt%7B6%7D+%2B++%5Csqrt%7B6%7D++++%7D%7B4%7D++%3D+++%5Cfrac%7B2+%5Csqrt%7B6%7D+%7D%7B4%7D+%3Cstrong%3E%3D++%5Cfrac%7B+%5Csqrt%7B6%7D+%7D%7B2%7D++)
sen (30 + 45) = sen 30° . cos 45° + sen 45° . cos 30°
sen (75°) =
sen 75° =
sen 75° =
cos (a+b) = cos a . cos b - sen a . sen b
cos ( 45 + 60) = cos 45° . cos 60° - sen 45° . sen 60°
cos (105°) =
cos 105º =
cos 105° =
Sen 75° - cos 105° =
Sen 75° - cos 105° =
ellengames:
Ind o gabarito da essa resposta só que negativa
Perguntas interessantes
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás